Korelasi Ekspresi PD-L1 dengan TILs CD8+ pada Kanker Paru Jenis Karsinoma Bukan Sel Kecil - Utami, Erisca Ayu; Ika Kartika, Ika Kartika; Rusminan, Suly Auline; Erial Bahar, Erial Bahar; Krisna Murti, Krisna Murti (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2021)
BackgroundNon-small cell lung cancer (NSCLC) is an epithelial carcinoma of the lung which consists of adenocarcinoma, squamous cellcarcinoma (SCC), and large-cell carcinoma (LCC). In a microtumor environment, PD-L1 and PD-1 bonds are immune checkpointsthat act in suppressing the activity of CD8+ TILs, thus affecting the prognosis of NSCLC. Aims of this study is to determine thecorrelation between PD-L1 expression with CD8+TILs in NSCLC.MethodsThis was a cross-sectional study of NSCLC registered in Department of Anatomical Pathology Faculty of Medicine University ofSriwijaya/Dr. Moh. Hoesin Palembang Hospital since 1 January 2017 to 31 January 2020 with a total of 24 samples. All sampleswere immunostained using PD-L1 and CD8 antibodies. PD-L1 expression was assessed in tumor mass and CD8 expression inintratumoral and peritumoral TILs.ResultsOnly two subtypes, adenocarcinoma and SCC, were found in this study. Adenocarcinoma was the most frequent subtype (54.1%),sample group is dominated by <60 years old and was the subtype that expressed the PD-L1 most strongly (TPS â‰¥50%). There wasnot significant correlation between PD-L1 expression with CD8+ TILs in NSCLC (p=0.679 and p=0.826) but based onclinicopathological characteristics, there was a significant relationship between PD-L1 with disease stage and between intratumoralCD8+ TILs density with disease stage (p=0.048 and p=0.017).ConclusionAdenocarcinoma subtype had stronger expression of PD-L1 compared to SCC. There was no correlation between PD-L1 and CD8+TILs density in NSCLC.